Representasi Visual Islam Berkemajuan dalam Konten Instagram @LensaMu: Analisis Semiotika Roland Barthes - Naufal Abiyuna Hadi; Iman Sumarlan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines how the Instagram account @LensaMu represents the concept of Islam Berkemajuan through visual-based digital da’wah. As religious communication increasingly operates within visual and social media environments, it becomes important to understand how Islamic values are constructed and conveyed through images and captions. This research employs a qualitative approach using Roland Barthes’ semiotic framework, focusing on the levels of denotation, connotation, and myth. The data consist of selected Instagram posts published by @LensaMu during the period January 2025 to December 2025, chosen through purposive sampling based on their relevance to themes of Islamic values, social ethics, and Muhammadiyah’s organizational identity. The analysis reveals four dominant representational patterns: (1) modern religiosity expressed through minimalist visual design and contemporary aesthetics; (2) civic ethics emphasizing social responsibility, humanitarian action, and public compassion; (3) organizational identity narratives that reinforce Muhammadiyah’s reformist and rational Islamic orientation; and (4) digital da’wah as a medium of informal religious learning through visually accessible content. These findings indicate that Instagram functions not only as a communication platform but also as a space where Islamic meanings are symbolically constructed and circulated. This study contributes to discussions on Islamic digital media by demonstrating how semiotic strategies shape the visual representation of Islam Berkemajuan in contemporary online da’wah practices.